1. -5Y^-2Z =

2. 1/4X^-3 =

Thank you for the opportunity to help you with your question!

First, we use this power law: U^-n = 1/U^n ; where n is the exponent or power of the base U.

So then we would have:

1.) -5Y^-2 Z = -5(1/Y^2)(Z) = (- 5Z)/(Y^2)

2.) 1/4X^-3 = (1/4)(1/X^3) = 1/(4X^3)

Please let me know if the second exercise is read like: 1/(4X^-3) or (1/4)X^-3.

I'm reading like 1/4X^-3 is 1/4 times X^-3 ---------> (1/4)X^-3

you read it correctly. The only issue I have is that the answers are really not any less simple than the original math problems.

Secure Information

Content will be erased after question is completed.

Enter the email address associated with your account, and we will email you a link to reset your password.

Forgot your password?

Sign Up